Functional rehabilitation of the maxillary sinus after modified endoscopic sinus surgery for displaced dental implants - Buyanbileg Sodnom-Ish; Mi Young Eo; Ju Young Lee; Mi Hyun Seo; Soung Min Kim (SpringerOpen, 2023)
Abstract Purpose Dental implants may become displaced into the maxillary sinus due to insufficient primary stability, changes in nasal air pressure, or surrounding bone resorption and should be removed as soon as possible. The aim of this study was to evaluate the efficacy of the modified endoscopic sinus surgery (MESS) approach for removal of displaced dental implants. Methods From September 2010 to November 2021, we studied 15 cases with displaced implants in the maxillary sinus. The patient characteristics, medical history, clinical and imaging results, and post-removal outcomes were retrospectively assessed. Results The symptoms included sinusitis (100%), pain (26.6%), postnasal drip (6.6%), nasal obstruction (26.6%), and oroantral communication (26.6%). Two cases were managed through the crestal approach (13.3%), while two cases were treated with the Caldwell-Luc procedure (13.3%). One case was addressed using functional endoscopic sinus surgery (6.7%), while 10 cases were managed with the MESS approach (66.7%). MESS allows functional rehabilitation of mucociliary clearance by the cilia in the sinus membrane. Implant displacement into the maxillary sinus can be classified as early, late, or delayed displacement. Conclusions MESS is a reliable treatment option that can identify migrated dental implants in any part of the sinus with endoscopic assistance for functional rehabilitation of the maxillary sinus without postoperative sequelae.